RE-AIM evaluation of the Veterans Health Administration’s MOVE! Weight Management Program - Kahwati, Leila C (Springer-Verlag, 2011)
Over one-third of patients treated in the Veterans Health Administration (VHA) are obese. VHA introduced the MOVE! Weight Management Program for Veterans in 2006 to provide comprehensive weight management services. An evolving, periodic evaluation using the RE-AIM framework (reach, effectiveness, adoption, implementation, and maintenance) has been conducted to gauge success and opportunities for improvement. Key metrics were identified in each RE-AIM dimension. Data were compiled over fiscal years (FY) 2006 through 2010 from a variety of sources including VHA administrative and clinical databases, electronic medical record reviews, and an annual, structured VHA facility self-report. REACH: Screening for obesity and offering weight management treatment to eligible patients increased from 66% to 95% over the past 3 years. MOVE! is currently provided at every VHA hospital facility and at over one-half of VHA community-based outpatient clinics. The percent of eligible patients who participate in at least one weight management visit has doubled since implementation began but has stabilized at 10 to 12%. EFFECTIVENESS: About 18.6% of the 31,854 patients with available weight data who participated in at least two treatment visits between Jul 1, 2008 and Sep 30, 2009 had at least a 5% body weight loss by 6 months as did almost one-third of those who participated in more intense and sustained treatment. By contrast, only 12.5% of a comparison group of patients matched on age, gender, body mass index (BMI) class, and comorbidity status who were not treated with MOVE! had at least a 5% body weight loss. ADOPTION: The median full-time staff equivalent providing weight management services at each facility has increased over time and was 1.76 in FY 2010. IMPLEMENTATION: Staff from multiple disciplines typically provide MOVE!-related care although not all disciplines are involved with providing care at every facility. Group-based treatment has become increasingly utilized, and in FY 2010 it represented 72% of all MOVE!-related visits. Intensity of treatment has increased from an average of 3.6 visits per patient per year in FY 2007 to 4.6 in FY 2010, but more than half of patients have two visits or less. Almost all facilities now report the consistent use of key evidence-based behavioral strategies with patients. MAINTENANCE: While participation in MOVE! by patients continues to grow each year, facility self-reported program staffing and space/equipment challenges are potential barriers to long-term program maintenance. Evidence-based weight management treatment can be delivered at VHA medical centers and community-based outpatient clinics, but the REACH remains limited after several years of implementation. Intense and sustained treatment with MOVE! results in a modest positive impact on short-term weight loss outcomes, but a relatively small proportion of patients engage in this level of care. Increasing reach, improving effectiveness of care, and keeping patients engaged in treatment are areas for future policy, practice, and research. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13142-011-0077-4) contains supplementary material, which is available to authorized users.